Research progress of T cell autophagy in autoimmune diseases - Zhao, Xingxing; Ma, Dan; Yang, Baoqi; Wang, Yajing; Zhang, Liyun (Frontiers in Immunology, 2024)
T cells, as a major lymphocyte population involved in the adaptive immune response, play an important immunomodulatory role in the early stages of autoimmune diseases. Autophagy is a cellular catabolism mediated by lysosomes. Autophagy maintains cell homeostasis by recycling degraded cytoplasmic components and damaged organelles. Autophagy has a protective effect on cells and plays an important role in regulating T cell development, activation, proliferation and differentiation. Autophagy mediates the participation of T cells in the acquired immune response and plays a key role in antigen processing as well as in the maintenance of T cell homeostasis. In autoimmune diseases, dysregulated autophagy of T cells largely influences the pathological changes. Therefore, it is of great significance to study how T cells play a role in the immune mechanism of autoimmune diseases through autophagy pathway to guide the clinical treatment of diseases.